Water Conservation Practices viewed from Community Socio-Psychological Factors (Case Study: Bandar Lampung City, Indonesia) - Rifka Noor Azizah; Dwi Marisa Putri; Ahmad Daudsyah Imami; Elinda Mutiara; Yulisa Putri; Nasrul Putra; Dion Awfa; Rahma Yanda; Zenia F. Saraswati; Endang Setiawati; Wisnu Prayogo (International Journal of Marine Engineering Innovation and Research, 2024)
Climate change that is happening at this time affects the decrease in the availability of water in the world. Urban areas, especially coastal areas, will have a more significant impact on water scarcity. Coastal areas in Indonesia, such as Bandar Lampung City, are mainly concerned in this study. Therefore, a study was conducted to determine the variables that influence water conservation practices in Bandar Lampung, which focuses on social psychological factors with four independent variables. By knowing the independent variable that has the highest level of influence, an approach to conservation efforts at the individual level can be approached. Data were obtained using a closed questionnaire with answer options using a Likert scale. Data analysis used simple linear regression and stepwise regression. The simple linear regression results show that the variable social norms (X4) are the highest variable with a value of R2 0.0385. In stepwise regression, the variable attitude towards conservation (X1), the benefits obtained (X2), individual control behavior (X3), and social norms (X4) simultaneously have a coefficient of determination value of R2 0.06127, where the social norms variable align with sample linear regression results on water conservation practices. These social norms can be used as a reference by stakeholders such as Perumda, Regional Government, NGOs, etc., through individual approaches in mapping strategies for increasing water conservation practices.